Principales hongos que afectan a Pinus tropicalis morelet en Cuba - Guerra, C.=700 1 Cruz, H.; Vila, I.; Duarte, A.; Lopez, M.O.
(Es, En)
Ilus., 25 ref.
Keywords: PINUS; HONGOS ENTOMOPATOGENOS; ENFERMEDADES FUNGOSAS; PINUS TROPICALES